Responsibility of PT Antam Tbk. on the Gold Purchase Dispute Against Budi Said (Case Study of the Decision of the Supreme Court Number 1666 K/Pdt/2022) - Stella Dea Firsty; Elwi Danil; Yussy Adelina Mannas (Dinasti Research, 2025)
Budi Said, as an individual, entered into a gold sale and purchase agreement with PT. Antam Tbk, which later became a dispute because PT. Antam Tbk failed to fulfill its obligations as per the agreement. The agreement in question was an underhand sale and purchase agreement. The issues to be examined in this case are as follows: first, the considerations of the judges in the Supreme Court decision related to the gold purchase dispute between PT. Antam Tbk and Budi Said; second, the responsibility of PT. Antam Tbk in this dispute based on Supreme Court decision number 1666 K/Pdt/2022; and third, how legal protection is provided to Budi Said regarding the unlawful actions of PT. Antam Tbk. This study employs a normative juridical approach with both a case approach and a statute approach. The data sources include secondary data consisting of primary, secondary, and tertiary legal materials. To analyze the first issue, the theory of legal certainty is applied, while the theory of responsibility is used for the second issue, and the theory of legal protection is used for the third issue. In this case, there is a discrepancy between the decisions of the lower courts (judex factie) and the Supreme Court (judex juris), which violates the principle of legal certainty. In Supreme Court decision number 1666 K/Pdt/2022, PT. Antam Tbk was found to have committed an unlawful act by failing to deliver the remaining 1.1 tons of gold from the total of 7 tons agreed upon, a failure that involved the company’s employees. PT. Antam Tbk was also held responsible for the losses suffered by Budi Said. Based on this Supreme Court decision, Budi Said received repressive legal protection, which applies after the dispute has occurred and is in the form of sanctions or compensation.